The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jpm11030209
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Separation Followed by Chronic Mild Stress in Adulthood Is Associated with Concerted Epigenetic Regulation of AP-1 Complex Genes

Abstract: Depression is one of the most prevalent mental diseases worldwide. Patients with psychiatric diseases often have a history of childhood neglect, indicating that early-life experiences predispose to psychiatric diseases in adulthood. Two strong models were used in the present study: the maternal separation/early deprivation model (MS) and the chronic mild stress model (CMS). In both models, we found changes in the expression of a number of genes such as Creb and Npy. Strikingly, there was a clear regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Over the past few decades, there has been mounting evidence that adverse childhood experiences can affect how individuals respond to both disease and treatment [65]. Many studies showed that childhood adversity can cause epigenetic changes [66] and increase an individual's susceptibility to various illnesses, such as cancer, heart disease, endocrine disorders and mental illnesses [67,68]. Likewise, the findings of the current study provide supporting evidence that mice exposed to early life stress by being separated from their mothers (from day 1 to 30 postnatal) were more likely to exhibit aberrant behaviors than their non-separated peers.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, there has been mounting evidence that adverse childhood experiences can affect how individuals respond to both disease and treatment [65]. Many studies showed that childhood adversity can cause epigenetic changes [66] and increase an individual's susceptibility to various illnesses, such as cancer, heart disease, endocrine disorders and mental illnesses [67,68]. Likewise, the findings of the current study provide supporting evidence that mice exposed to early life stress by being separated from their mothers (from day 1 to 30 postnatal) were more likely to exhibit aberrant behaviors than their non-separated peers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of c-Jun in the hypothalamus and serum AP-1 in the SP600125 group decreased significantly in the model group after the inhibition of JNK signaling pathway by SP600125, indicating that c-Jun and AP-1 are key regulators in the pathogenesis of depression. Similarly, previous studies have reported that the stressinduced upregulation of the molecules in JNK signaling pathway, including c-Fos, c-Fun, and p-JNK, might be involved in the pathogenesis of depression (Huguet, Kadar, Temel, & Lim, 2017;Lundgaard Donovan et al, 2021;Meng, Wang, & Luo, 2019). Moreover, clinical studies have also shown that c-Fos gene expression is upregulated in depressed patients, and may lead to the deterioration of patients' survival (Yi, Liu, Wu, Wu, & Zhang, 2019).…”
Section: Discussionmentioning
confidence: 72%
“… 74 Expression of the transcription factor cAMP response element-binding protein and neuropeptide Y and a reduction of Jun-B mRNA have been reported after MS. Jun-B is one of four genes in the activator protein-1 complex that could be epigenetically regulated. 75 ELS triggers epigenetic modifications in genes outside the HPA axis, including BDNF, the serotonin transporter (5-HTT or Slc6a4) gene, the estrogen receptor-α gene, glutamate decarboxylase-1, and Reelin genes. 71 …”
Section: Resultsmentioning
confidence: 99%